Efficiency of an Alternative Physical Education Program for the Lower Grades of Elementary School Children - Jovan Marković; Saša Bubanj; Goran Šekeljić; Slobodan Pavlović; Marko Radenković; Dušan Stanković; Emilija Petković; Nikola Aksović; Oliver Radenković; Adem Preljević; Bojan Bjelica; Vladan Petrović; et al. (MDPI AG, 2023)
(1) Introduction: This research was conducted with the aim of assessing whether an alternative physical education (PE) program could effectively substitute for the traditional PE curriculum and aid in accomplishing the essential goals and objectives of PE among younger elementary school children. (2) Materials and Methods: This longitudinal 6-month study included third-grade elementary school children of both genders, who were healthy, lived in urban areas, and were involved in an alternative PE program, as well as the regular PE classes. The sample of participants comprised 214 students, with 105 participants in the experimental group and 109 participants in the control group, who underwent pre- and post-intervention measurements. For the purposes of this study, 11 variables were applied to assess the parameters of growth and development, motor abilities, and physical and health education. MANCOVA and ANCOVA methods were used to determine the effects resulting from the alternative and regular PE programs, and differences between the groups, respectively. The data are reported as the mean and standard deviations, and were analyzed using the statistical package SPSS version 20.0 (SPSS Inc., Armonk, NY, USA). (3) Results: Based on the research results obtained for motor abilities and physical and health education, it was concluded that both the alternative and regular PE programs had positive effects in achieving the goals and objectives of PE, but without statistical significance at the multivariate and univariate levels. The differences between the two groups were found to be negligible (effect size, ES < 0.2). (4) Discussion: Sports and PE have distinct objectives and approaches. While sports emphasize competition and winning, PE aims to impart fundamental skills and knowledge, prioritizing inclusivity among younger students. Success in PE is measured by the number of students meeting these goals, potentially affecting both talented and struggling learners. (5) Conclusions: The results obtained from the conducted research indicate that both the alternative PE program and the regular PE program influence changes in motor abilities and physical and health education to a limited extent. The alternative PE program proposed in this study, with its modifications to the structure of existing, regular PE program, can fully replace the latter in schools that do not meet the required spatial and material standards.